Combined Dietary Nitrate and Exercise Intervention in Peripheral Artery Disease: Protocol Rationale and Design - Woessner, Mary N (JMIR Res Protoc, 2017)
BACKGROUND: Peripheral artery disease (PAD) is caused by atherosclerotic occlusions in the legs. It affects approximately 8-12 million people in the United States alone, one-third of whom suffer from intermittent claudication (IC), defined as ischemic leg pain that occurs with walking and improves with rest. Patients with IC suffer a markedly impaired quality of life and a high perception of disability. Improving pain-free walking time is a primary goal of rehabilitation in this population. OBJECTIVE: The nitric oxide (NO)-PAD trial is designed to compare the effects that 12 weeks of supervised exercise training, in combination with a high inorganic nitrate-content (beetroot [BR] juice) beverage or placebo (PL) beverage, has on clinical outcomes of exercise and functional capacity in two groups of PAD+IC patients: exercise training plus beetroot (EX+BR) and exercise training plus placebo (EX+PL). The primary aims of this randomized controlled, double-blind pilot study are to determine group differences following 12 weeks of EX+BR versus EX+PL in the changes for (1) exercise capacity: pain-free walking time (claudication onset time, COT), peak walk time (PWT), and maximal exercise capacity (peak oxygen uptake, VO(2peak)) during a maximal-graded cardiopulmonary exercise test (max CPX) and (2) functional capacity: 6-minute walk (6MW) distance. The secondary aims will provide mechanistic insights into the exercise outcome measures and will include (1) gastrocnemius muscle oxygenation during exercise via near-infrared spectroscopy (NIRS); (2) gastrocnemius muscle angiogenesis: capillaries per unit area and per muscle fiber, and relative fraction of type I, IIa, IIb, and IId/x fibers; and (3) vascular health/function via brachial artery flow-mediated dilation, lower-limb blood flow via plethysmography, and pulse wave velocity and reflection. METHODS: A total of 30 subjects between 40 and 80 years of age with PAD who are limited by IC will undergo exercise training 3 days per week for 12 weeks (ie, 36 sessions). They will be randomized to either the EX+BR or EX+PL group where participants will consume a beverage high in inorganic nitrate (4.2 mmol) or a low-nitrate placebo, respectively, 3 hours prior to each training session. RESULTS: Data collection from this study has been completed and is in the process of analysis and write-up. While the study is too underpowered—EX+BR, n=11; EX+PL, n=13—to determine between-group differences in the primary outcomes of COT, PWT, and 6MW, preliminary observations are promising with Cohen d effect sizes of medium to large. CONCLUSIONS: Exercise training is currently the most effective therapy to increase functional capacity in PAD+IC. If the addition of inorganic nitrate to an exercise regimen elicits greater benefits, it may redefine the current standard of care for PAD+IC. TRIAL REGISTRATION: ClinicalTrials.gov NCT01684930; https://clinicaltrials.gov/ct2/show/NCT01684930 (Archived by WebCite at http://www.webcitation.org/6raXFyEcP)